1989
DOI: 10.1073/pnas.86.21.8266
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order structure of Saccharomyces cerevisiae chromatin.

Abstract: We have developed a method for partially purifying chromatin from Saccharomyces cerevisiae (baker's yeast) to a level suitable for studies of its higher-order folding. This has required the use of yeast strains that are free of the ubiquitous yeast "killer" virus. Results from dynamic light scattering, electron microscopy, and x-ray diffraction show that the yeast chromatin undergoes a cation-dependent folding into 30-nm filaments that resemble those characteristic of higher-cell chromatin; moreover, the packi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 23 publications
3
50
0
1
Order By: Relevance
“…In addition, S. cerevisiae chromatin structure has been reported to have little or no linker DNA between nucleosomes, which would preclude ladder formation [49]. The ability of yeast to die in an apoptotic-like manner is consistent with the idea that programmed cell death was in place before the divergence of yeast and metazoans.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In addition, S. cerevisiae chromatin structure has been reported to have little or no linker DNA between nucleosomes, which would preclude ladder formation [49]. The ability of yeast to die in an apoptotic-like manner is consistent with the idea that programmed cell death was in place before the divergence of yeast and metazoans.…”
Section: Discussionsupporting
confidence: 60%
“…Again, these data draw parallels to observations of PCD in animal cells where the defining characteristics include nuclear pyknosis and DNA fragmentation. These parallels are significantly furthered by the recent report that yeast cells harbor a cysteine protease distantly related to mammalian caspases, designated metacaspases [49]. The yeast metacaspase not only has structural, but also functional homology to mammalian caspases.…”
Section: Discussionmentioning
confidence: 94%
“…Nuclease fragmentation and isolation of native chromatin fibers results in nucleosome chains coated with nonhistone "husks" (24) that obscure transmission electron microscopy imaging (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Although the budding yeast is thought to lack HI histone (Perez-Ortin et al 1989), a functional HI homolog was demonstrated recently (Lowary and Widom 1989). In addition, active genes in yeast and higher eukaryotes display similar functional features, i.e., enhanced sensitivity to singlestranded endonuclease SI and DNase I at sites flanking the active genes (for reviews, see Weintraub 1985;PerezOrtin 1989), indicating an alteration of nucleosomal organization in the promoter and coding regions upon gene activation.…”
mentioning
confidence: 99%
“…The budding yeast Saccharomyces cerevisiae and higher eukaryotes share several common features of chromatin structure, including nucleosomal organization, folding of chromatin into higher-order structures, as well as the conservation observed for transcriptional machinery (Weintraub 1985;Guarente 1988;Lowary and Widom 1989;Perez-Ortin et al 1989). Although the budding yeast is thought to lack HI histone (Perez-Ortin et al 1989), a functional HI homolog was demonstrated recently (Lowary and Widom 1989).…”
mentioning
confidence: 99%